Neural substrate of cognitive theory of mind impairment in amyotrophic lateral sclerosis. (April 2015) - Carluer, Laurence; Mondou, Audrey; Buhour, Marie-Sonia; Laisney, Mickaël; Pélerin, Alice; Eustache, Francis; Viader, Fausto; Desgranges, Béatrice
Abstract: We now know that amyotrophic lateral sclerosis (ALS) is not restricted to the motor system. Indeed, a large proportion of patients with ALS exhibit cognitive impairment, especially executive dysfunction or language impairment. Although researchers have recently turned their attention to theory of mind (ToM) in ALS, only five studies have been performed so far, and they reported somewhat contradictory results. Moreover, the neural basis of the potential ToM deficit in ALS remains largely unknown. The present study was therefore designed to clarify whether a cognitive ToM deficit is indeed associated with ALS, specify the putative link between cognitive ToM deficits and executive dysfunction in ALS, and identify the dysfunctional brain regions responsible for any social cognition deficits. We investigated cognitive ToM and executive functions in a group of 23 patients with ALS and matched healthy controls, using an original false-belief task and a specially designed battery of executive tasks. We also performed an 18 F-fluorodeoxyglucose positron emission tomography examination. Results confirmed the presence of cognitive ToM deficits in patients compared with controls, and revealed significant correlations between ToM and executive functions, although the cognitive ToM deficit persisted when a composite executive function score was entered as a covariate. Using statistical parametric mapping, we calculated positive correlations between tracer uptake and false-belief scores on a voxel-by-voxel basis in the patient sample. Results showed that the cognitive ToM deficit correlated with the dorsomedial and dorsolateral prefrontal cortices, as well as the supplementary motor area. Our findings provide compelling clinical and imaging evidence for the presence of a genuine cognitive ToM deficit in patients with ALS.